Rapid and Multiplex Diagnosis of Malaria Using Chelex-100 Extraction and LAMP-MS Assay - Min Lim; Young Choe; Woong Jang (Bio-Protocol)
Malaria remains a major public health threat, especially in tropical and subtropical regions. Accurate and rapid diagnosis is essential for effective disease management and control, yet conventional malaria diagnostics, including blood smear microscopy using Giemsa staining, PCR, and rapid diagnostic tests (RDTs), are limited by the need for trained personnel, reliance on laboratory infrastructure, and reduced sensitivity at low parasite densities, respectively. This protocol details an innovative, rapid, and economical diagnostic platform combining a simplified Chelex-100 resin-based nucleic acid extraction method with a multiplex loop-mediated isothermal amplification microscanner (LAMP-MS) assay. The malaria diagnostic platform enables simultaneous detection of Plasmodium falciparum (Pf), Plasmodium vivax (Pv), pan-malaria (Pan), and an internal control (IC) within 40 min, from DNA extraction to result interpretation. It demonstrates sensitivity and specificity comparable to traditional PCR-based diagnostics, making it a practical and scalable solution for use in resource-constrained environments.